Analisis Struktur dan Nilai Pendidikan Hindu yang terkandung Dalam Cerita Watugunung Perspektif Desa Bulian - Pujayanti, Ni Kadek Ayu Gita; Wiyantari, Ni Nengah; Ayu, Ni Kadek; Putriyani Dewi, Ni Luh PT. (Dharma Sastra : Jurnal Penelitian Bahasa dan Sastra Daerah, 2024)
This research analyzes the structure and values ​​of Hindu education contained in the Watugunung story based on the perspective of the people of Bulian Village, Bali. The Watugunung story is one of the important mythological stories in Balinese tradition which has various narrative variations in each region. The Bulian Village version displays different story elements and characterization compared to the widely circulated version. The analysis in this article covers two main aspects, namely, intrinsic and extrinsic elements. This research found that the local interpretation of Bulian Village not only enriches understanding of the Watugunung story, but also emphasizes moral and spiritual education that is relevant to Hindu teachings. The results of this research provide new insight into how local traditions and myths can act as a means of religious learning and character formation in the Balinese Hindu community. These findings also show that local variations in narratives do not reduce the essence of Hindu teachings, but instead enrich their meaning and application in people's lives.